The Baltic tiger: The political economy of Estonia's transition from plan to market - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2008)
Few countries have reformed their economies as swiftly and decisively as Estonia in 1992-94. The economic reform program started during the Perestroika, and intensified in the first year of independence. Yet it was in 1992, amid the collapsing economy and under new political leadership, that the comprehensive reform program started. The establishment of a currency board arrangement, a swift move to zero tariffs, and a solid and transparent privatization program were key parts of this reform era. Fredrik Erixon documents these reforms in a new paper The Baltic Tiger.
Keywords: 330